Low-power non-binary SAR ADC with a two-mode comparator - Li, Jianni (2015)
For implantable medical devices like artificial pacemakers, high power efficiency is demanded because they are supposed to work 5 to 10 years on a battery. ADC is one of the major blocks as the interface between analog signals and digital logic. Hence, low power ADC with low speed and medium resolution is needed for such applications. These requirements make SAR ADC a suitable choice due to its simple structure and serial operation. However, there is still room for future power efficiency improvement.